School experiences of transgender and gender diverse students in Australia. Issue 2 (3rd March 2016) - Jones, Tiffany; Smith, Elizabeth; Ward, Roz; Dixon, Jennifer; Hillier, Lynne; Mitchell, Anne
Abstract: Over the last decade, there has been an increase in global and local policy protections on the basis of gender identity and expression in education and a recent spate of coverage of transgender students on Australian television and news media. This paper explores the school experiences of Australian transgender and gender diverse students', with particular consideration of recognition of their gender identity in documentation, experiences of puberty and sexuality education, treatment by staff and students, and other forms of provision. It reports on the findings of a 2013 study which combined a survey of 189 transgender and gender diverse Australian students aged 14–25 years, with 16 online interviews with members of this group. The study was informed by a community advisory group which included a range of transgender, gender diverse and intersex people. Findings include both quantitative and qualitative data, detailing a trend towards more disruptive, fluid and inconsistent identifications by members of this student group, and a diversification of their needs at school. Student advocacy on topics including sexuality and puberty education was shown to be common and also useful in improving individual well-being and social outcomes. We offer some reflections towards more useful school practices and future research.